Blinkenberg og Høybyes Dansk-Fransk og Fransk-Dansk Ordbog – fra seddelsamling til trykte ordbøger og til onlineudgave - Schøsler, Lene (LexicoNordica, 2016)
The Danish-French and French-Danish dictionaries elaborated by Andreas Blinkenberg and Margrethe Thiele, subsequently by Blinkenberg and Poul Høybye are influential and large bilingual Danish dictionaries, the 1997 editions comprising respectively 172,000 Danish lemmas and more than 1 million translations of words and expressions into French, and some 83,000 French lemmas and more than 1 million translations into Danish. The paper discusses the lexicographical principles of the dictionaries and presents a number of predictable and unpredictable problems, which arise when transferring printed dictionaries to an electronic platform.